Biogeographic trajectories from Gondwana to the present in two families of landhoppers (Amphipoda, Talitroidea), with the description of a new family - Myers, Alan A. (Zootaxa, 2026)
The currently defined landhopper family Brevitalitridae is divided into two families, the Brevitalitridae sensu stricto and the Spelaeorchestiidae fam. nov. The biogeographic trajectories leading to their current distributions are hypothesised. The possible loss of cusps on the dactyls of walking legs in a landhopper is signalled.